BORYS GRINCHENKO IDEAS ABOUT THE PURPOSE AND OBJECTIVES OF THE NATIONAL SCHOOL - Kolyadenko, Olga V. (Educological discourse, 2016)
The article deals with Boris Grinchenko ideas of the purpose and objectives of the national school. Analyzed the works of the outstanding teacher and interpretative intelligence successors of Ukrainian scientists of the last third of the twentieth century on Boris Grinchenko’s considerations about the purpose and objectives of development of the ukrainian national school. It was shown that a teacher had proved necessity of the organization of the school, which had the national educational content and the spirit, would be publicly available, teach in the native language and interact with the social environment.